2011
DOI: 10.1186/1476-4598-10-80
|View full text |Cite
|
Sign up to set email alerts
|

Irinotecan induces steroid and xenobiotic receptor (SXR) signaling to detoxification pathway in colon cancer cells

Abstract: BackgroundResistance to chemotherapy remains one of the principle obstacles to the treatment of colon cancer. In order to identify the molecular mechanism of this resistance, we investigated the role of the steroid and xenobiotic receptor (SXR) in the induction of drug resistance. Indeed, this nuclear receptor plays an important role in response to xenobiotics through the upregulation of detoxification genes. Following drug treatments, SXR is activated and interacts with the retinoid X receptor (RXR) to induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…The active metabolite SN-38 (7-ethyl-10-hydroxylcamptothecin) of irinotecan is primarily inactivated by UGT1A1. Studies have shown that overexpression of UGT1A1 in a lung cancer cell line (PC-7/CPT) (Oguri et al, 2004) or induction of UGT1A1 by SN-38 in colon (LS180) and liver (HepG2) cancer cell lines is associated with irinotecan resistance (Basseville et al, 2011). The induction of UGT2B7 by its substrate EPI described in the present study may represent a new example of this type of regulation.…”
Section: Discussionmentioning
confidence: 85%
“…The active metabolite SN-38 (7-ethyl-10-hydroxylcamptothecin) of irinotecan is primarily inactivated by UGT1A1. Studies have shown that overexpression of UGT1A1 in a lung cancer cell line (PC-7/CPT) (Oguri et al, 2004) or induction of UGT1A1 by SN-38 in colon (LS180) and liver (HepG2) cancer cell lines is associated with irinotecan resistance (Basseville et al, 2011). The induction of UGT2B7 by its substrate EPI described in the present study may represent a new example of this type of regulation.…”
Section: Discussionmentioning
confidence: 85%
“…In recent years have been described several genetic polymorphisms that affect the expression of this gene (Chu and Fyles, 2007). CYP3A4 protein expression has been observed in cancer tissues (Takahara et al, 2011;Weiss and Haefeli, 2011) due the induction of different kind of substances, resulting in an increase in transcription and expression of CYP3A4 (Basseville et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, CYP3A4 phenotype, as assessed by midazolam clearance, is significantly associated with irinotecan pharmacokinetic (Mathijssen et al, 2004). More recently, a study suggested that the Pregnane X-Receptor (PXR) pathway is also involved in irinotecan resistance in colon cancer cell line via the upregulation of drug-metabolizing genes such as CYP3A4 (Basseville et al, 2011).…”
Section: Involvement Of Cytochrome P450smentioning
confidence: 99%